2022
DOI: 10.3390/ijms23116236
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy-Mediated Regulation of Different Meristems in Plants

Abstract: Autophagy is a highly conserved cell degradation process that widely exists in eukaryotic cells. In plants, autophagy helps maintain cellular homeostasis by degrading and recovering intracellular substances through strict regulatory pathways, thus helping plants respond to a variety of developmental and environmental signals. Autophagy is involved in plant growth and development, including leaf starch degradation, senescence, anthers development, regulation of lipid metabolism, and maintenance of peroxisome ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 123 publications
(141 reference statements)
0
10
0
Order By: Relevance
“…Besides, now it is an established fact that IAA production by microbes is a direct plant growth promontory mechanism, as IAA assists in plant growth, root proliferation, tissue differentiation, elongation, embryonic development, etc. ( Egamberdieva, 2011 ; Cheng et al., 2022 ). In the present study, a considerable amount of IAA production was reported by both i.e., P. jesenii MP1 and P. palleroniana N26 cold adaptive bioinoculants ranging from 28.03 ± 0.97 and 41.38 ± 1.26 µg/ml, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, now it is an established fact that IAA production by microbes is a direct plant growth promontory mechanism, as IAA assists in plant growth, root proliferation, tissue differentiation, elongation, embryonic development, etc. ( Egamberdieva, 2011 ; Cheng et al., 2022 ). In the present study, a considerable amount of IAA production was reported by both i.e., P. jesenii MP1 and P. palleroniana N26 cold adaptive bioinoculants ranging from 28.03 ± 0.97 and 41.38 ± 1.26 µg/ml, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, we observed that the terms of autophagy, mitophagy, and ubiquitin-mediated proteolysis were significantly enriched by transcriptome analysis, and subsequently, the remarkable increase in the level of autophagosome was confirmed by fluorescent staining in the Δ Aopex14/17 mutants. Autophagy plays a vital role in the maintenance of peroxisome mass, and autophagy further regulates peroxisomes and contributes to the production of ROS ( 41 ). Peroxisome abundance can be regulated by PEX genes.…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy has many biological functions in plants, and it is closely related to plant growth, development, flowering, and fruiting ( Cheng et al., 2022 ). It will also cause autophagy when exposed to exogenous biotic or abiotic stress.…”
Section: Discussionmentioning
confidence: 99%